2000
DOI: 10.1093/treephys/20.9.629
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf trichomes of Wigandia urens: environmental factors and physiological consequences

Abstract: Seasonal and environmentally induced variation in the type and frequency of leaf trichomes of Wigandia urens (Ruiz & Pavón) Kunth (Hydrophyllaceae) was studied. Depending on the microsite, W. urens plants had smooth leaves with glandular trichomes or bristly leaves with both glandular trichomes and urticant trichomes (stinging hairs). Trichome density (number of urticant trichomes per unit leaf area) was higher in the dry season than in the wet season, and was significantly correlated with both temperature (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 9 publications
4
69
1
1
Order By: Relevance
“…Genotype and environmental conditions also likely affect trichome densities. In Wigandia urens, for instance, a higher light intensity increased the trichome density (Pérez-Estrada et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Genotype and environmental conditions also likely affect trichome densities. In Wigandia urens, for instance, a higher light intensity increased the trichome density (Pérez-Estrada et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…However, because these traits also reduce the loss of water in leaves ( HeideJørgensen, 1990 ;Oertli et al, 1990 ) and increase the dissipation of solar radiation ( Ehleringer and Cook, 1990 ;Woodman and Fernandes, 1991 ;Pérez-Estrada et al, 2000 ), toughness and trichomes could also be selected by the abiotic environment prevailing in the sand dunes of the study site. Leaf toughness can play a major role in plant survival and performance, particularly at our study site where soils are highly permeable with low water and nutrient retention Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the trichome density is closely related to temperature, light, soil moisture, wounding, and other factors in various plant species (Wellso and Hoxie, 1982;Gianfagna et al, 1992;Pé rez-Estrada et al, 2000;Yoshida et al, 2009). It will be interesting to examine the regulation of trichome production by these exogenous and endogenous cues and their crosstalk with the miR156/SPLs pathway.…”
Section: Discussionmentioning
confidence: 99%